THE INFLUENCE OF TEACHERS’ PERCEPTIONS OF PRINCIPALS’ SUPERVISION MANAGEMENT ON WORK STRESS LEVELS AND PSYCHOLOGICAL WELL-BEING - Khafidhoh; Ahmadi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Teachers’ psychological health has become a critical issue in contemporary schooling, particularly as accountability demands and evaluative pressures intensify supervisory practices. Teachers’ perceptions of how principals manage supervision are increasingly recognized as a key determinant of occupational stress and psychological well-being. This study aims to examine the influence of teachers’ perceptions of principals’ supervision management on work stress levels and psychological well-being. The study employed a quantitative correlational design using a cross-sectional survey approach. Data were collected from teachers through standardized questionnaires measuring perceived supervision management, work stress, and psychological well-being, and were analyzed using descriptive statistics and inferential techniques, including correlation and regression analyses. The results indicate that teachers’ perceptions of supervision management significantly predict both outcomes. Positive perceptions of supportive, transparent, and developmental supervision are associated with lower work stress and higher psychological well-being, whereas negative perceptions of controlling supervision correspond to increased stress and reduced well-being. Supervision management demonstrates a meaningful explanatory contribution to teachers’ psychological conditions. Enhancing principals’ supervisory approaches with attention to teachers’ perceptions may reduce occupational stress and promote sustainable psychological well-being. Such efforts strengthen leadership effectiveness and support healthier professional environments within schools through sustainable, ethical, and psychologically informed supervision practices nationwide implementation.